2013
DOI: 10.1186/1477-7525-11-208
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Irritable Bowel Syndrome Quality of Life (IBS-QOL) questionnaire in diarrheal-predominant irritable bowel syndrome patients

Abstract: BackgroundDiarrhea-predominant irritable bowel syndrome (IBS-d) significantly diminishes the health-related quality of life (HRQOL) of patients. Psychological and social impacts are common with many IBS-d patients reporting comorbid depression, anxiety, decreased intimacy, and lost working days. The Irritable Bowel Syndrome Quality of Life (IBS-QOL) questionnaire is a 34-item instrument developed and validated for measurement of HRQOL in non-subtyped IBS patients. The current paper assesses this previously-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 27 publications
1
75
0
1
Order By: Relevance
“…про-педевтики внутренних болезней и гастроэнтерологии; тел. : +7(499)187-1097; e-mail: svch555362@yandex.ru номическими затратами на лечение, но и влиянием на качество жизни (КЖ) больных СРК, которое значительно ниже теоретически нормального уровня по всем оценива-емым критериям [4]. Более того, оно сопоставимо с тако-вым при хронической сердечной недостаточности, воспа-лительных заболеваниях кишечника и сахарном диабете, а у больных СРК и запором снижение КЖ сопоставимо с КЖ пациентов, страдающих ревматоидным и псориати-ческим артритом [5][6][7].…”
Section: терапевтический архив 2 2015unclassified
“…про-педевтики внутренних болезней и гастроэнтерологии; тел. : +7(499)187-1097; e-mail: svch555362@yandex.ru номическими затратами на лечение, но и влиянием на качество жизни (КЖ) больных СРК, которое значительно ниже теоретически нормального уровня по всем оценива-емым критериям [4]. Более того, оно сопоставимо с тако-вым при хронической сердечной недостаточности, воспа-лительных заболеваниях кишечника и сахарном диабете, а у больных СРК и запором снижение КЖ сопоставимо с КЖ пациентов, страдающих ревматоидным и псориати-ческим артритом [5][6][7].…”
Section: терапевтический архив 2 2015unclassified
“…A major risk factor in the onset of MC-associated disorders, including allergy, asthma, and IBS, is life stress [5][6][7]. Experimental studies in animal models and humans have reported a link between psychologic stressors and increased tissue MC activation and pathophysiology, including inflammation and intestinal permeability [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhoea in adults is a common complaint and, while rarely life‐threatening outside of developing countries, it continues to be an important cause of morbidity . Symptoms can cause distress and incapacitate sufferers, significantly impacting on health‐related quality of life . The precise clinical presentation, time course and management requirements are dependent on the underlying pathological determinants.…”
Section: Introductionmentioning
confidence: 99%
“…1 Symptoms can cause distress and incapacitate sufferers, 2 significantly impacting on health-related quality of life. 3 The precise clinical presentation, time course and management requirements are dependent on the underlying pathological determinants. Current guidelines classify diarrhoea as either acute 1,2,4 or chronic.…”
Section: Introductionmentioning
confidence: 99%